The Role of International Organizations in Conflict Resolution: Case Studies of the UN and EU in Africa - Dantata, Bello S. (Kashere Journal of Politics and International Relations, 2025)
The role of international organizations in conflict resolution is crucial in maintaining global peace and security, particularly in conflict-prone regions such as Africa. This study examines the involvement of the United Nations (UN) in resolving conflicts on the continent, with a focus on its peacekeeping missions, mediation efforts, sanctions, and diplomatic interventions. Using the Democratic Republic of Congo (MONUSCO) and Sudan (UNAMID and UNITAMS) as case studies, the research evaluates the effectiveness, successes, and challenges of the UN's interventions. The findings reveal that while the UN has made significant contributions in reducing large-scale violence, supporting democratic transitions, and providing humanitarian assistance, its missions often struggle with logistical challenges, political constraints, and operational inefficiencies. The study highlights the need for enhanced collaboration between the UN, regional organizations such as the African Union (AU), and local governance structures to ensure sustainable peace. The paper concludes that structural reforms, increased funding, and stronger political will are essential for improving the effectiveness of UN-led conflict resolution efforts in Africa.